Kajian Faktor Sosial Ekonomi Penambang Emas di Desa Ratatotok Satu Kecamatan Ratatotok Kabupaten Minahasa Tenggara - Vriska Rani Sumendap; Hilda Vemy Oroh; Kalvin Salindeho Andaria; Ellen Eva Poli (Fakultas Ilmu Sosial dan Hukum, 2023)
This study aims to analyze the socio-economic influences on the income of gold miners in Ratatotok Satu Village, Ratatotok District, Southeast Minahasa Regency. Research variables of land, costs, technology, labor, and skills. This research uses a quantitative descriptive method. The results of a study, most of the mining land belongs to other people. With their capital, miners finance their operations in small groups at each mining point or tunnel. Miners have been proficient at mining for less than ten years. Most of the miners are elderly.